The Role of Social Studies Education and Character Development of Students at MI Fathul Ulum Kalicilik, Bojonegoro - Rifai Rifai; Deni Pratiwi; Faridatul Lailiyah; Anggraeni Ratridite Sudarso (Journal of Social Studies Education and Humanities Research, 2024)
The Role of Social Studies Learning and Character Development of Students at MI Fathul Ulum Kalicilik. This research aims to analyze how social studies materials can support character values such as honesty, responsibility, and tolerance. The study employs a descriptive qualitative method, with data collected through interviews and observations. The subjects of this research are the teachers and students of MI Fathul Ulum Kalicilik. The findings indicate that interactive and contextual learning methods in social studies can enhance students’ social awareness and foster positive behavior. Therefore, social studies play a crucial role in supporting the educational vision of the Madrasah